Pengaruh Latihan Plyometric di Pasir Untuk Meningkatkan Kemampuan Smash Atlet Bola Volly Universitas Muhammadiyah Palopo - Azzahra Junantri; Rasyidah Jalil; Firmansyah Dahlan; Fajri Hamzah (Jurnal Porkes, 2026)
The low smash ability of volleyball athletes at the Muhammadiyah University of Palopo Club is due to a lack of structured training programs and appropriate coaching methods. This study aims to evaluate the effect of plyometric training on sand on improving the athletes’ smash ability. The study used a quantitative approach with a one-group pretest-posttest design. The sample consisted of 10 male athletes aged 20–24 years who were selected using simple random sampling. The instrument used was a volleyball smash accuracy test with a validity of 0.80 and a reliability of 0.88. Plyometric training in the form of depth jumps on sand was administered over 16 sessions at a frequency of three times per week. Data analysis utilized descriptive statistics and a paired-sample t-test. The results showed an increase in average smash ability from 6.90 on the pretest to 10.60 on the posttest, with a difference of 3.70. The paired-sample t-test yielded a calculated t-value (12.333) > table t-value (2.262) with a significance level of 0.001 < 0.05, indicating a highly significant effect. The conclusion of this study is that plyometric training on sand has a significant effect on improving the smash ability of volleyball athletes at Muhammadiyah University of Palopo.